Family Roles in Overcoming Picky Eating Children and Its Effect on Childs’ Nutrition Status - Antonia, As Syifa; Chairani, Liza; Fitrianti, Yuni; Purwoko, Mitayani (Indonesian Journal of Medical Anthropology, 2025)
Nutritional status is a measuring scale based on the body's condition due to food consumption or nutritional intake. Picky eating is a behavior that often occurs in preschool children, which can affect the child's nutritional status. The role of parents is very influential in overcoming picky eaters. This study aimed to understand the role of the family in overcoming picky eater behavior in children and to measure the nutritional status of children with picky eater behavior at Kindergarten X Palembang. This study was qualitative research with a phenomenological approach. The informants were mothers of picky eating children based on CEBQ criteria. The data were collected using in-depth interviews and anthropometric measurements, and the data was analyzed quantitatively. This research found that parents played a role in trying to overcome picky eater behavior in children Including restrictive guidance, pressure to eat, rewarding food consumption materially, rewarding with praise, accessibility, however, their child's picky eater behavior was not resolved, and based on the results of anthropometric measurements, most children with picky eater behavior had normal nutritional status (64.7%). In comparison, 17.64% of children experience wasted nutritional status, 11.7% are severely wasted, and 5.8% are obese.